The Red-Green Alliance: A roaring, yet harmless lion - Seeberg, Henrik (Politica, 2020)
The Red-Green Alliance (RGA) rose from the ashes of three dying communist parties when the Berlin wall fell in 1989, and has enjoyed remarkable success. RGA has become an established, stable part of the far left in the Danish Folketing. What explains this success? RGA can be described as a roaring, but harmless lion in the sense that RGA asks more questions to the minister than any other party in the Danish parliament; mainly about social welfare, the environment, and the EU. Yet, this pressure on the government is not converted into policy influence in the annual budget when it would be most likely, namely during Social Democratic cabinets. Through its criticism (but not its policy influence), RGA has been able to challenge the executive and maintain a pure, uncompromising ideological stance during a time characterized by welfare cuts, immigrant restrictions, and a rising climate crisis. A growing group of voters has been looking for this type of party.